Sorgo em dietas para o Jundiá (Rhamdia quelen) - Rabelo, Pedro Carvalho (2014)
The aim of this study was to evaluate the effect of replacing corn by sorghum low tannins in diets for silver catfish (Rhamdia quelen) on growth performance and survival of the fish, the chemical composition of the carcass, in two hematological parameters - total protein and leukocytes - and size and density of micro villi of the fish. The experiment was conducted at the Instituto de Pesquisa em Aquicultura Ambiental - InPAA belonging to Universidade Estadual do Oeste do Paraná, Toledo campus. Six hundred fingerlings with initial average weight and length of 4.49 ± 0.8 grams and 3.42 ± 0.24 inches respectively were distributed in 24 tanks - network with capacity 1m3 of usable volume. Completely randomized design with six treatments and four replications was used with an experimental unit formed by tank with 25 fish. Treatments consisted of six diets with increasing levels of 0; 6; 12; 18; 24; 30% sorghum and decreasing 30; 24; 18; 12; 6; 0% corn.. For 114 days, the fingerlings were fed three times a day (8, 12 and 17h), ad libitum. Survival was lower in the lot of fish fed a diet containing 30% sorghum, differing significantly (p <0.05) diets with 0 and 6% sorghum. The values of the chemical composition of the carcass and total protein were normal for the species and may serve as a basis for comparison with studies involving different culture conditions of silver catfish. It was concluded that sorghum can replace corn by 80% in diets for silver catfish.